From Bottom to Top: Challenge on Formulating New Value Blueprint - Anita Maharani; Harry Sutanto; Synthia Atas Sari; Dianti Arudi (Jurnal Pengabdian Pada Masyarakat, 2019)
This paper aims to disseminate an experiential report of a program conducted for Mitsubishi Pet Film Indonesia (MFI) to change the organization. The company asked us to develop both blueprint report and visual guidance report and disseminate it through nine workshops conducted to Change Agent (CA). We as consultant work together with the company to determine Change Agent, through Focus Group Discussion within 70 employees chosen by the company, then selected 25 out of 70 who then become the Change Agent. We implement John P. Kotter, known as Kotter’s 8 Step Change Model during the process, both us and the company realize that although change process has been made, it would not place any effect until a post Majeure event. By one event, when there was a fire in one of the company’s installation, Change Agents were trained to implement change as the company hoped it.